A hotel life cycle model based on bootstrap DEA efficiency. Issue 5 (13th July 2015) - Yin, Pengzhen; Tsai, Henry; Wu, Jie
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to propose a hotel life cycle model and applies this model to examine the development of international tourist hotels (ITHs) in Taipei. Design/methodology/approach – In this study, a two-stage approach is proposed to examine the life cycles of 20 ITHs in Taipei. First, we evaluate the overall and departmental efficiencies by using a two-layer bootstrap data envelopment analysis (DEA) model. Second, we divide the phases of the hotel life cycle by incorporating two objective indicators, namely, the average efficiency change rate (AECR) and the annual average efficiency (AE). Findings – The results show not only that the efficiency scores derived from the bootstrap DEA model could help assess the performance of individual ITHs but also that the resulting AECR and AE could help to objectively classify the development of the hotels under study into the following phases: initial, growth, maturity and recession and regeneration phases. Practical implications – The method proposed in, and the results obtained from, this study can provide the stakeholders of the ITHs in Taipei with an alternative to the existing subjective enterprise life cycle (ELC) model for identifying these ITHs' stages of development using quantitative and objective criteria. Originality/value – Existing hotel management research rarely focuses on hotel life cycle analysis, likely due to the adoption of subjective criteria by the conventional ELC model, which limits the practical application of the research. To improve on the conventional ELC model, our proposed quantitative approach involves dividing the hotel life cycle by employing two objective indicators and then empirically presenting the results.